2016
DOI: 10.1007/s40825-016-0051-1
|View full text |Cite
|
Sign up to set email alerts
|

Urea-Water-Solution Properties: Density, Viscosity, and Surface Tension in an Under-Saturated Solution

Abstract: A temperature-concentration dependent surface fit for the relative viscosity of a urea-water-solution (UWS) is calculated based on experimental and literature data. For the surface fit, a 2D Lorenzian function was used, where the xaxis was assigned to a urea mass fraction and the y-axis to the solution temperature and the rest of the parameters were optimized based on the experimental and literature data. The surface model describes the relative viscosity of undersaturated urea-water-solution (UWS). The experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…However, this error is further minimized because of the use of a similar concentration of internal standards such as TEA + or TMA + to evaluate the half-wave potentials of the target ions. Another complication is the effect of the increased viscosity of the 8 M urea of 1.66 mPa s 17 on the half-wave potential. As described in the Supporting Information, this effect will shift the half-wave potentials by 6 mV toward more negative potentials.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…However, this error is further minimized because of the use of a similar concentration of internal standards such as TEA + or TMA + to evaluate the half-wave potentials of the target ions. Another complication is the effect of the increased viscosity of the 8 M urea of 1.66 mPa s 17 on the half-wave potential. As described in the Supporting Information, this effect will shift the half-wave potentials by 6 mV toward more negative potentials.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…This indicates that urea-water-solution surface tension is not greatly different than water at ambient conditions. Birkhold [23] reported a slightly higher surface tension for AdBlue compared to water, while Halonen [47] indicated that UWS surface tension slightly increases with urea concentration.…”
Section: Urea-water-solution (Uws)mentioning
confidence: 99%
“…Recently surface tension measurements supported by MD-simulations showed that the surface tension increases proportionally with the urea concentration. 16 20 Previous vibrational sum-frequency generation (VSFG) spectroscopy studies of solutions containing α-lactalbumin and urea showed that the orientation of the amide groups of the protein at the surface is independent from that of the urea molecules. This observation suggests that there are no strong direct interactions between the amide groups of the protein and the urea molecules, and points at an indirect denaturation process of the protein.…”
mentioning
confidence: 99%
“…Up to now, primarily the properties of urea in the bulk of aqueous solutions have been studied, and little work has been done addressing the properties of urea at aqueous surfaces. Recently surface tension measurements supported by MD-simulations showed that the surface tension increases proportionally with the urea concentration. Previous vibrational sum-frequency generation (VSFG) spectroscopy studies of solutions containing α-lactalbumin and urea showed that the orientation of the amide groups of the protein at the surface is independent from that of the urea molecules. This observation suggests that there are no strong direct interactions between the amide groups of the protein and the urea molecules, and points at an indirect denaturation process of the protein. , In this work, we perform heterodyne-detected VSFG (HD-VSFG) measurements to investigate the molecular response of urea molecules at charged aqueous interfaces, by measuring the effect of the surface charge on the vibrational response of urea.…”
mentioning
confidence: 99%